Genetic distance estimation of local swamp buffaloes through morphology analysis approach. - Anneke Anggraeni; C. Sumantri; L. Praharani; Dudi .; E. Andreas (Jurnal Ilmu Ternak dan Veteriner, 2011)
Information about genetic distances among populations (geographics) of local swamp buffalo is less published. Genetic distance analysis was done among seven local swamp buffalo populations trhough a morphological analysis. Female and male buffaloes were observed for a total number of 905 hds, originating from the Provices of NAD (100 hds), North Sumatera (51 hds), Banten (180 hds), Central Java (203 hds), South Kalimantan (121 hds), NTB (200 hds), dan South Sulawesi (50 hds).  Genetic variation among buffalo populations was calculated by discriminant function of Mahalonobis distance. Genetic distance was estimated by MEGA program. Morphometric measurements of female buffalo in North Sumatera were larger (P < 0,01) than those of buffaloes in Banten, South Kalimantan, NAD and South Sulawesi. Morphometric measurements of male buffalo in South Sulawesi were larger than those of buffaloes in Central Java, Banten, and NAD. Chest width was the highest different morphometric factor (0.969). Buffalo from NTB had the highest similarity (95.0%), followed by buffaloes from North Sumatera (74.51%) and South Sulawesi (74.19%); while the lowest one was from South Sulawesi (38.02%) and Banten (49.44%). Morphological distribution map indicated existence of three local swamp buffalo groups. Grup 1 was presented by buffalo from NTB, distributed in the II and III quadrants. Group 2 was presented by buffaloes from five locations (North Sumatera, Central Java, South Kalimantan, South Sulawesi, and Banten), distrributed in I and II quadrants, and a smaller part distributed in III and IV quadrants. Group 3 was presented by buffaloes from NAD and a smaller part from South Kalimantan and Banten, distributed in IV quadrant. The lowest genetic distance was identified between buffaloes in NAD and South Kalimantan (0.348), while the highest one was between buffloes in Banten and South Kalimantan (1.883). Based on phenogram tree structure, the observed local swamp buffaloes could be classified into 3 cluster, namely: Cluster 1 from South Kalimantan, NAD and Banten; Cluster 2 from South Sulawesi, Central Java and North Sumatera, and Cluster 3 from NTB. Key Words: Swamp Buffalo, Morphology, Discriminant Analysis, Genetic Distance